Differences in factors associated with postpartum hemorrhage in developed and developing countries: A systematic review - Handayani, Sri Astuti; Kartini, Farida (Majalah Obstetri & Ginekologi, 2025)
HIGHLIGHTS Analysis of maternal and fetal risk factors associated with postpartum hemorrhage, comparing data from both developed and developing countries. There are differences in the risk factors for postpartum hemorrhage between developed and developing countries.   ABSTRACT Objective: This study aimed to assess maternal and fetal risk factors for post-partum hemorrhage in both developed and developing countries. Materials and Methods: A systematic review methodology was employed, incorporating a descriptive design. The study followed Joanna Briggs Institute (JBI) techniques, the PCC framework, and the PRISMA-ScR checklist. Article searches were conducted across four databases: Research Rabbit, Science Direct, Wiley, and PubMed. Articles published in English between 2019 and 2024 that met the inclusion criteria were selected. The search terms included combinations of “Postpartum women” OR “Puerperium” AND “Risk factors” OR "Risky conditions” AND “Postpartum hemorrhag*” “Postpartum bleeding” and “Developed countr*” AND “Developing countr*”. Results: Out of 906 articles, 20 met the inclusion criteria, representing both developed and developing countries. The findings were categorized into two themes: risk factors in developed versus developing countries. In developed countries, PPH risk factors are often linked to medical interventions and prolonged labor management, while in developing countries, the focus shifts to conditions like anemia, uterine overdistension, and trauma from delivery practices. Sociocultural disparities further exacerbate risks in both settings. Conclusion: The study reveals significant differences in PPH risk factors between developed and developing countries. By reviewing existing research, it identifies factors that can influence PPH occurrence. The findings emphasize the need for developing policies to screen pregnant, maternity, and postpartum women to mitigate PPH risk.